Respuesta :
3, 9, 15, 21, 27,…
+6 +6 +6 +6
a(n) = a₁ + d(n - 1)
a(n) = 3 + 6(n - 1)
a(n) = 3 + 6(n) - 6(1)
a(n) = 3 + 6n - 6
a(n) = 6n + 3 - 6
a(n) = 6n - 3
a(n) = 6n - 3
a(25) = 6(25) - 3
a(25) = 150 - 3
a(25) = 147
+6 +6 +6 +6
a(n) = a₁ + d(n - 1)
a(n) = 3 + 6(n - 1)
a(n) = 3 + 6(n) - 6(1)
a(n) = 3 + 6n - 6
a(n) = 6n + 3 - 6
a(n) = 6n - 3
a(n) = 6n - 3
a(25) = 6(25) - 3
a(25) = 150 - 3
a(25) = 147
Answer: 147
Step-by-step explanation:
The given arithmetic sequence : 3, 9, 15, 21, 27, ….....................
From the above sequence, it can be seen that the first term [tex]a= 3[/tex]
The common difference = [tex]d=9-15=21-15=6[/tex]
We know that in arithmetic sequence, the nth term is given by :-
[tex]a_n=a+d(n-1)[/tex]
Then for, n=25, the 25th term will be :-
[tex]a_{25}=3+6(25-1)\\\\\Rightarrow\ a_{25}=147[/tex]